2020
DOI: 10.31234/osf.io/r4p5z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Predicting Willingness to Share COVID-19 Misinformation

Abstract: We conducted a preregistered exploratory survey to assess whether patterns of individual differences in political orientation, social dominance orientation, traditionalism, conspiracy ideation, or attitudes about science predict willingness to share different kinds of misinformation regarding the COVID-19 pandemic online. Analyses revealed two orthogonal models of individual differences predicting the willingness to share misinformation over social media platforms. Both models suggest a sizable role of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…In contrast, an exploratory survey which was run to assess whether patterns of individual differences in political orientation, social dominance orientation and traditionalism may predict the willingness to share different kinds of misinformation regarding the COVID-19 pandemic online showed that liberals with a low disposition toward social dominance are specifically less willing to share conspiratorial misinformation than are conservatives with a high disposition toward social dominance, at least regarding a culturally salient scientific topic [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, an exploratory survey which was run to assess whether patterns of individual differences in political orientation, social dominance orientation and traditionalism may predict the willingness to share different kinds of misinformation regarding the COVID-19 pandemic online showed that liberals with a low disposition toward social dominance are specifically less willing to share conspiratorial misinformation than are conservatives with a high disposition toward social dominance, at least regarding a culturally salient scientific topic [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be associated with denialism: a predisposition to reject information from experts and official accounts of major events, and major predictor of COVID-19 conspiracy theories 20 . Similarly, general scepticism about science is correlated with a greater willingness to spread various kinds of misinformation about COVID-19, including conspiracy claims 75 . In countries with less belief in science (indexed by prevalence of climate sceptics) adherence to physical distancing measures is also lower 76 .…”
Section: Beliefs Biases and Attitudesmentioning
confidence: 99%
“…States, for example, conservative individuals tend to hold stronger beliefs in COVID-19 conspiracy theories than liberals 12,20,46,79 , perceive less personal vulnerability and rate the virus as less severe 79 , potentially as reaction to criticism concerning handling of the pandemic by the Republican president at the time 46 . Conservatives are also less accurate than liberals at discerning between real and fake headlines 79 and are more willing to spread conspiracy-themed misinformation online 75 . In a sample comprising mostly Americans, political conservatism, religious orthodoxy, and conspiracist ideation was associated with less trust in science, which explained their unwillingness to adhere to safeguarding behaviours 80 .…”
Section: Social Factorsmentioning
confidence: 99%
“…The situation of Covid-19 put persons in isolation. Social media is the only way for spending time and reduces the chances of depression (Lobato E, Powell M., Padilla L, & Holbrook C, 2020).This research explains the role of media from the context of maintaining peace and security of people during the pandemics. It further explains the misinformation through media leads to panic and fear among people.…”
Section: Review Of Literaturementioning
confidence: 86%